Microscopy of Ashoka Bark and Marketed Alternates. - Rana , C S; Raturi, P P; Rai, R K (International Research Journal of Ayurveda & Yoga, 2023)
Introduction- Microscopic evaluation of herbal powder is the simplest method for the identification of raw materials or raw drugs. Today, many sophisticated modern research tools are available for the identification validation and authentication of plant based drugs. Ashoka (Saraca asoca) has been used traditionally in the Indian system of medicine. Internal structure (cells and tissues) of bark of the Asoka, Shal and Kastdaru have been studied through plant anatomy/histology. Material & Methods-Raw drug sample powder of all species were dipped in water and centrifuged for five minutes to soften and sedimentation. Suspended material of the sample was transferred to a clean glass micro slide and mounted. Slides were observed under axiostar plus light microscope. Results & Discussion- The Powder Microscopic method is still one of the inventive methods for validation and authentication of the raw drugs. It also helps to find out the impurities and helps in quality assessment and assurance of the drugs. Microscopic assessment of the herbal drug of Asoka (Saraca asoca Roxb. Willd) shows similarity and some dissimilarity with cells and tissues of the bark of Shal (Shorea robusta Gaertn.) and Kastdaru (Polyalthia longifolia Sonn. Thwaites) for the selection of possible alternates.